The Early Age Strength Improvement of the High Volume Fly Ash Mortar - Kaoutar Bazzar; Fatima Zahra Hafiane; Adil Hafidi Alaoui (Civil Engineering Journal, 2021)
In the last decade, the use of Fly ash as replacement to improve the strength and performance of the cement has become a part of mortar and concrete manufacturing. When the used amount of fly ash ranges from 20 to 25%, the proprieties of concrete and mortars such as strength and durability are improved, which also reduce the Portland cement consumption and its impact on environment. For some special applications the High-Volume Fly Ash (HVFA) (up to 50%) is recommended, but the use of HVFA is still limited because of the low early age strength. The aim of this study is to overcome the constraints caused by the use of the High-Volume Fly Ash, by upgrading the mortar using grinding to reduce the particle size, and by the application of an upsetting force to modify the behavior of swelling and to modify the crystal structure of ettringite in order to increase the early age strength of the mortar. The results show an increase in the rupture resistance at 7 days and 28 days by 60% and 30% respectively. Which will make the use of HVFA mortar possible in construction industry and therefore reduce more CO2 emissions from the cement production. Doi: 10.28991/cej-2021-03091731 Full Text: PDF